Síntese, caracterização e estudo do comportamento térmico do cocristal de glibenclamida com trometamina - SILVA FILHO, Silvério Ferreira da (2016)
Glibenclamide (GLB) is a sulphonylurea used as oral antidiabetic indicated for the control of blood glucose in patients of diabetes mellitus type 2. It belongs to the class II of the Biopharmaceutics Classification System (BCS), because it has high membrane permeability, low aqueous solubility and low bioavailability. The cocrystals drugs are presented as an alternative for improving bioavailability and increased its therapeutic effectiveness. This study aimed to the synthesis, characterization and study of thermoanalytical cocrystals of GLB using as coformers tromethamine (TRIS). Therefore, the cocrystals of GLB with TRIS were synthesized by slow evaporation of solvent and grinding assisted solvent (mechanochemical). Thereafter, the cocrystals were characterized by X-ray diffraction by the powder method (PXRD) absorption spectroscopy in the infrared Fourier transform spectroscopy (FTIR) absorption spectroscopy in the near infrared region (NIR), Raman spectroscopy, thermogravimetry and simultaneous differential thermal analysis (TG/DTA), differential scanning calorimetry (DSC), DSC cyclic and DSC photovisual. They were also performed conformational studies of the interaction of GLB with the TRIS for the investigation of the binding sites of these compounds in the formation of the co-crystal. Furthermore was performed diagrams the construction of the binary phases of GLB-TRIS system. Conformational studies showed that the major binding sites in the GLB were sulfonamide carbonyl oxygens and the amide grouping while in TRIS are from one of amine nitrogen and oxygen atoms. From the PXRD results verified the formation of cocrystals by obtaining a new crystalline structure. The FTIR results indicate the formation of a new material and it was possible to suggest some binding sites and correlates them with the results of conformational studies. The results obtained in the NIR and Raman spectroscopy supported those obtained in FTIR, allowing affirm again the formation of cocrystals. Then, TG/DTA curves indicated the stability of cocrystals and DSC curves indicated a single defined peak, and that compound. We conducted further characterization by DSC photovisual, proving the event obtained in the DSC curves and finally the cyclic DSC curves showed the relative stability of cocrystals categorized as irreversible after the fusion event. Therefore, from the results we obtained it was observed that interacts with the GLB e TRIS, resulting in the formation of cocrystals molar ratio of 1: 1 by slow solvent evaporation and solvent assisted by milling. The methodology presented is most advantageous for the synthesis of cocrystals, as it requires less time and fewer solvent. This study showed the formation of cocrystals between GLB and TRIS (1:1) for both methodologies used and it was possible to suggest the main functional groups involved in training through theoretical calculation (computer analysis) and experimentally by FTIR, NIR and Raman. Therefore, the results obtained in this study were critical to the synthesis and spectroscopic and thermal characterization of cocrystals of GLBTRIS and may subsidize studies to cocrystals synthesis of other sulfonylureas and the production of more effective antidiabetic pharmaceutical formulations for the treatment of diabetes mellitus type 2.